Endovascular embolization of cervical hemangiopericytoma with Onyx-18: case report and review of the literature. (8th December 2010) - Santillan, Alejandro; Zink, Walter; Lavi, Ehud; Boockvar, John; Gobin, Y Pierre; Patsalides, Athos
Abstract : Cervical hemangiopericytoma (HPC) is a rare tumor involving dura and bone. Because HPC shares some imaging features with meningioma, hemangioblastoma, schwannoma and solitary fibrous tumors; histology with appropriate immunohistochemistry is essential for its diagnosis and treatment. HPC is highly vascular and has a high rate of local recurrence following resection. Thus it can pose significant therapeutic challenges. To the best of our knowledge this is the 13th reported case of HPC of the cervical spine and the first case of cervical HPC treated using embolization with Onyx-18. In addition, a systematic review of the literature is presented describing previous experience with HPC of the cervical region. The case of a 61-year-old woman is reported who presented with a 7 month history of dizziness, mild ataxia and left-sided tinnitus when supine. MRI of the cervical spine demonstrated a gadolinium enhancing mass arising from the dorsal cervical dura, extending from the occiput to C2, with internal flow voids and extension into the C2 lamina and spinous process. Digital subtraction angiography demonstrated multiple corkscrew-shaped supplying vessels, marked hypervascularity, rapid arteriovenous shunting and delayed contrast washout. Super selective injection of Onyx-18 yielded approximately 90% embolization of the lesion, followed by subtotal resection and radiotherapy. Histology confirmed the presumptive diagnosis of HPC. Preoperative embolization with Onyx-18 should be considered for large HPC as it may decrease the risk of intraoperative hemorrhage. In this case, embolization with Onyx-18 did not preclude histopathologic diagnosis of HPC.